Effect of Electronic Nudges on Influenza Vaccination Rate in Older Adults With Cardiovascular Disease: Prespecified Analysis of the NUDGE-FLU Trial. Issue 18 (5th March 2023) - Modin, Daniel; Johansen, Niklas Dyrby; Vaduganathan, Muthiah; Bhatt, Ankeet S.; Lee, Simin Gharib; Claggett, Brian L.; Dueger, Erica L.; Samson, Sandrine I.; Loiacono, Matthew M.; Køber, Lars; Solomon, Scott D.; Sivapalan, Pradeesh; et al.
Abstract : Background: Influenza vaccines have been demonstrated to effectively reduce the incidence of influenza infection and potentially associated risks of cardiovascular events in patients with cardiovascular disease (CVD). Despite strong guideline and public health endorsements, global influenza vaccination rates in patients with CVD are highly variable. This prespecified analysis of NUDGE-FLU (Nationwide Utilization of Danish Government Electronic Letter System for Increasing Influenza Vaccine Uptake) examined the effect of digital behavioral nudges on influenza vaccine uptake based on the presence of CVD. Methods: NUDGE-FLU was a randomized, pragmatic, nationwide, register-based trial that included Danish citizens 65 years of age or older during the 2022 to 2023 influenza season. Households were randomized in a 9:1:1:1:1:1:1:1:1:1 ratio to usual care or 9 electronic letters with designs based on behavioral concepts. Danish nationwide registers were used to collect baseline and outcome data. The primary end point was receipt of an influenza vaccine on or before January 1, 2023. The effects of the intervention letters were examined according to the presence of CVD and across cardiovascular subgroups that included heart failure, ischemic heart disease, and atrial fibrillation. Results: Of 964 870 NUDGE-FLU participants from 691 820 households, 264 392 (27.4%) had CVD. During follow-up, 83.1% of participants with CVD versus 79.2% of participants without CVD received an influenza vaccination ( P <0.001). Compared with usual care, a letter emphasizing the potential cardiovascular benefits of influenza vaccination increased vaccination rates; this effect was consistent in participants with CVD (absolute difference, +0.60 percentage points [99.55% CI, –0.48 to 1.68]) and without CVD (+0.98 percentage points [99.55% CI, 0.27–1.70; P for interaction=0.41). A repeated letter strategy with a reminder follow-up letter 14 days later was also effective in increasing influenza vaccination, irrespective of CVD (CVD: absolute difference, +0.80 percentage points [99.55% CI, –0.27 to 1.86]; no CVD: +0.67 percentage points [99.55% CI, –0.06 to 1.40]; P for interaction=0.77). Effectiveness of both nudging strategies was consistent across all major CVD subgroups. None of the other 7 nudging strategies were effective, regardless of CVD status. Conclusions: Electronic letter interventions emphasizing the potential cardiovascular benefits of influenza vaccination and using a reminder letter strategy were similarly beneficial in increasing influenza vaccination rates among older adults with and without CVD and across cardiovascular subgroups. Electronic nudges may improve influenza vaccine uptake in individuals with CVD. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT05542004.